APEX and the values of national transformation - Campbell, James (2010)
One of the most critical issues in regards to higher education is the relationship between education and the broader economic and social worlds. In the Malaysian context one of the more interesting issues in regards to the development of higher education and economic and social development is the relationship and synergies between the Accelerated Program of Excellence (APEX) university reform and the Governments transformation agenda articulated in One Malaysia, the Government Transformation Program and the New Economic Model.Economic modernization and globalization to which the New Economic Model (NEM) and APEX are important responses require complex theorization for us to adequately grasp and engage with. Questions for us to ponder as we consider the diverse ways in which we can understand the APEX program include: How can we maintain a commitment to values within a commitment to advancing scientific knowledge? How can we ensure that educational institutions produce innovative and creative students and yet also maintain core values? What is the relationship between APEX and National Development? To what extent is life long learning important to embed as a practice that can help Malaysia realise its national goals? Can a discussion of Universiti Sains Malaysia’s (USM) philosophy and approach under APEX case light on all these issues?